Economic study on the feasibility of building a standard model to predict wheat yield production in Iraq using the bootstrapping and time series method - Frahan, Alaa K.; Hatim, T.A.; Bandar, Sarah A. (Edelweiss Applied Science and Technology, 2025)
The wheat crop is of great importance in the agricultural economy and dietary pattern, as it represents the main source of bread in Iraq. To bridge the gap, production increased through the efficient use of economic resources. To minimize this problem, the Bootstrapping method is applied, while the time series analysis method ultimately resolves it, making the comparison between the two methods very important. Wheat yield data in Iraq were obtained from published and unpublished secondary sources, including the Ministry of Agriculture, the Ministry of Planning - Central Bureau of Statistics, and the Arab Organization for Agricultural Development in Iraq. Using SPSS (version 22), a model was developed to describe the relationship between production and costs, utilizing the Bootstrapping method and the time series method. Both equations explain 68% of the variation in wheat production, and both equations are statistically significant. However, the Bootstrapping method cannot determine the presence or absence of autocorrelation in residuals. Moreover, the time series method confirms that no autocorrelation exists between the residuals.